The Effectiveness of Playgrounds through Vegetated-Setting Approach in Tembalang, Indonesia - Widjajanti, Retno; Ristianti, Novia Sari (Semarang State University, 2020)
Abstract. As part of urban public space, playgrounds are a children's play space that can improve children's sensory, communication, and physical abilities. Playgrounds must be able to create comfort and education for children to engage with nature. One of the approaches to achieve is by the vegetated setting. Tembalang is a sub-district in Semarang, with children dominating 44% of the total population. Therefore, the playground's effectiveness in Tembalang was assessed based on comfort nature and connection with nature. Nine playgrounds are the object of this research. This study is aimed to determine the effectiveness level of the playground in Tembalang using the vegetated-setting approach. The research used a quantitative approach with Guttman-Scale scoring. This study's output assesses the level of effectiveness of the vegetated-setting playground through two aspects. The first aspect, comfort nature, which included in the effective level (71%) in the form of vegetation, protects children from heat and rain while playing, vegetation that provides shelter when children relax or gather under trees, vegetation can cause cold air and the condition of the grass field. It is comfortable to use and is not slippery. In comparison, the second aspect, the connection with nature, is included in the effective level (50%) in the form of plucked vegetation such as fruit or flowers, vegetation that can climb to train the child physically, vegetation that can bring animals to live in, such as birds or butterflies, and grass fields that children can use for running and physical activity.